Wafer-scale integration of GaAs/AlGaAs core–shell nanowires on silicon by the single process of self-catalyzed molecular beam epitaxy. Issue 6 (3rd February 2023) - Minehisa, Keisuke; Murakami, Ryo; Hashimoto, Hidetoshi; Nakama, Kaito; Sakaguchi, Kenta; Tsutsumi, Rikuo; Tanigawa, Takeru; Yukimune, Mitsuki; Nagashima, Kazuki; Yanagida, Takeshi; Sato, Shino; Hiura, Satoshi; et al.
Abstract : Optically efficient GaAs/AlGaAs core–shell nanowires on 2-inch Si wafers before (front right) and after (others) growth. The samples show a dark-colored feature indicating light absorption on the substrate surface. Abstract : GaAs/AlGaAs core–shell nanowires, typically having 250 nm diameter and 6 μm length, were grown on 2-inch Si wafers by the single process of molecular beam epitaxy using constituent Ga-induced self-catalysed vapor–liquid–solid growth. The growth was carried out without specific pre-treatment such as film deposition, patterning, and etching. The outermost Al-rich AlGaAs shells form a native oxide surface protection layer, which provides efficient passivation with elongated carrier lifetime. The 2-inch Si substrate sample exhibits a dark-colored feature due to the light absorption of the nanowires where the reflectance in the visible wavelengths is less than 2%. Homogeneous and optically luminescent and adsorptive GaAs-related core–shell nanowires were prepared over the wafer, showing the prospect for large-volume III–V heterostructure devices available with this approach as complementary device technologies for integration with silicon.